Big business and quality of institutions in the post-Soviet space: Spatial aspects - Alexander Libman (OrdnungsPolitisches Portal (OPO), 2007)
The spatial aspect of political-economic transformation in the former Soviet Union - including the relations between new independent states and the center-region relations within national borders - has a heavy impact on the quality of institutions comprising the economic order. The paper discusses how the interaction between the development of large business groups and changes in the spatial organization of power within the framework of the Russian federalism and the post-Soviet integration influenced the changes of economic institutions. In the 1990s the interests of big business contributed to the fragmentation of both internal market in Russia and international markets in the CIS and therefore to the general disorganization problem. Since 1998 development of interregional corporations supported the re-integration of the Russian market. Since 2000 the investment expansion of Russian business plays an important role for the integration from bellow in the post-Soviet space. Yet even in this case the impact on the quality of institutions is ambiguous: integration of markets influences the power relations between different levels of government in Russia and between different governments in the CIS. Moreover, it intensifies the processes of institutional competition, which have an ambiguous effect on the development of institutions because of the demand for bad institutions problem.
Keywords: 330; Russian Federation; CIS; transformation; spatial organization of power; bad institutions